Economic Activity of Groups Being in a Specific Situation in the Labour Market in the Lodz - Żmurkow-Poteralska, Edyta (Olsztyn Economic Journal, 2017)
The aim of this study is to determine the structure of economic activity among selected groups of individuals experiencing the greatest difficulties in the labour market, especially: people under the age of 30, people over the age of 50, persons with disabilities, women and people caring for dependents, as well as the characteristics of these particular groups. The study includes a deepened analysis of the employment structure by employment status, work contract and working time in the analysed groups. Also the reasons for part-time work and economic inactivity have been identified. The study uses cross-sectional data from the Labour Force Survey for the fourth quarter of 2013 as well as the data from The Assessment of Resources of Social Assistance in the Lodz Region for the year 2015 and covers the Lodz province.